A trio of quinoline-isoniazid-phthalimide with promising antiplasmodial potential: Synthesis, in-vitro evaluation and heme-polymerization inhibition studies. (1st June 2021) - Rani, Anu; Sharma, Anny; Legac, Jenny; Rosenthal, Philip J.; Singh, Parvesh; Kumar, Vipan
Graphical abstract: Synthesis of quinoline-isoniazid-phthalimide triads along with their antiplasmodial evaluation. Highlights: A library of Quinoline-isoniazid-phthalimide triads with antiplasmodial activities. The most potent compound exhibited IC50 11 nM against chloroquine resistant W2 strain of P. falciparum. Heme-binding studies were performed to delineate the mechanism of action. Abstract: Quinoline-isoniazid-phthalimide triads have been synthesised to assess their antiplasmodial efficacy and cytotoxicity against chloroquine-resistant W2 strain of P. falciparum and Vero cells, respectively. Most of the synthesized compounds displayed IC50 in lower nM range and appeared to be approximately five to twelve fold more active than chloroquine. Heme-binding studies were also carried out to delineate the mode of action. The promising compounds with IC50s in range of 11–30 nM and selectivity index >2800, may act as promising template for the design of new antiplasmodials.